A pointwise inequality for a biharmonic equation with negative exponent and related problems. (7th November 2018) - Ngô, Quốc Anh; Nguyen, Van Hoang; Phan, Quoc Hung
Abstract: Inspired by a recent pointwise differential inequality for positive bounded solutions of the fourth-order Hénon equation in with, p   >  1, due to Fazly et al (2015 Anal. Partial Differ. Equ .8 1541–63), first for some positive constants α and β we establish the following pointwise inequality in with for positive C 4 -solutions of the fourth-order equation where q   >  1. Next, we prove a comparison property for Lane–Emden system with exponents of mixed sign. Finally, we give an analogue result for parabolic models by establishing a comparison property for parabolic system of Lane–Emden type. To obtain all these results, a new argument of maximum principle is introduced, which allows us to deal with solutions with high growth at infinity. We expect to see more applications of this new method to other problems in different contexts.